Bosnia and Herzegovina : Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2002)
This report highlights Bosnia and Herzegovina's Request for Stand-By Arrangement (SBA). The authorities have requested a 15-month SBA in the amount of SDR 67.6 million (40 percent of quota) for June 2002-September 2003. Private investment and FDI remain mired in concerns over political risks, the hostile business environment, and infrastructure bottlenecks. Fixed investment outside government, construction, and reconstruction is low-perhaps 10 percent of GDP, and construction is slowing as aid inflows are curtailed. Significant fiscal consolidation appears to have been achieved in 2001 and fiscal structures have been strengthened.